Adoptive cell therapy: past, present and future. (January 2017) - Cohen, Jonathan E; Merims, Sharon; Frank, Stephen; Engelstein, Roni; Peretz, Tamar; Lotem, Michal
The immune system is a potent inhibitor of tumor growth with curative potential, constituting in many eyes the future of antineoplastic therapy. Adoptive cell therapy (ACT) is a form of immunotherapy in which autologous cancer-cognate lymphocytes are expanded and modified ex vivo and re-infused to combat the tumor. This review follows the evolvement of ACT and treatment protocols, focusing on unresolved dilemmas regarding this treatment while providing evidence for its effectiveness in refractory patients. Future directions of ACT are discussed, in particular with regard to genetic engineering of autologous cells, and the role of ACT in the era of checkpoint inhibitors is addressed.